Fenomena Bencana Banjir Sumatera atas Dugaan Penebangan Pohon yang Dikaitkan dengan Sistem Hukum Indonesia dan Hukum Perjanjian - Riskita Riskita; Muhammad Abdur rohim; Ni’matur Rohmah; Nur Faizah; Muslehatul Fa’izeh; Firza Agung Prakoso (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article explores legal accountability for flood disasters occurring in several regions of Sumatra, which are widely alleged to result from large-scale logging activities. The analysis is conducted within the framework of the Indonesian legal system, with particular emphasis on contract law. This study adopts a literature-based research method by examining statutory provisions, legal doctrines, and relevant scholarly publications. The analysis demonstrates that flood events should not be understood solely as natural occurrences, but rather as ecological consequences arising from the failure to fulfill contractual obligations embedded in forest utilization permits. From a contract law perspective, forestry concessions establish binding legal relationships that impose environmental protection duties on permit holders in accordance with the principle of pacta sunt servanda. Logging activities that exceed authorized limits may therefore be classified as contractual default (wanprestasi) and, at the same time, constitute unlawful acts that cause harm to the state and affected communities. Accordingly, this study underscores the necessity of strengthening environmental protection clauses within concession agreements and applying strict liability principles to enhance legal responsibility and prevent recurring environmental harm.